2014
DOI: 10.1101/gad.235499.113
|View full text |Cite
|
Sign up to set email alerts
|

The diabetes gene Hhex maintains δ-cell differentiation and islet function

Abstract: The homeodomain transcription factor HHEX (hematopoietically expressed homeobox) has been repeatedly linked to type 2 diabetes mellitus (T2DM) using genomewide association studies. We report here that within the adult endocrine pancreas, Hhex is selectively expressed in the somatostatin-secreting d cell. Using two mouse models with Hhex deficiency in the endocrine pancreas, we show that Hhex is required for d-cell differentiation. Decreased somatostatin levels in Hhex-deficient islets cause disrupted paracrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
124
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(130 citation statements)
references
References 33 publications
(31 reference statements)
5
124
1
Order By: Relevance
“…Surprisingly, mRNAs encoding all pancreatic hormones, including ghrelin, gastrin, glucagon, somatostatin, and pancreatic polypeptide, were upregulated in PAX6-deficient cells (even though only ghrelin could be detected at the protein level; Figure 4B and Supplemental Figure 5). We also observed upregulation of multiple TFs (Supplemental Table 2), including some known regulators of non-β cell programs, such as Hhex (a direct activator of somatostatin transcription) (42).…”
Section: Resultsmentioning
confidence: 94%
“…Surprisingly, mRNAs encoding all pancreatic hormones, including ghrelin, gastrin, glucagon, somatostatin, and pancreatic polypeptide, were upregulated in PAX6-deficient cells (even though only ghrelin could be detected at the protein level; Figure 4B and Supplemental Figure 5). We also observed upregulation of multiple TFs (Supplemental Table 2), including some known regulators of non-β cell programs, such as Hhex (a direct activator of somatostatin transcription) (42).…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, we observed that Cav1.2 expression was specifically regulated in pancreatic δ cells, but not in pancreatic β cells, owing to selective HHEX interactions ( Figure 6, J-M). The diabetes gene Hhex is specifically expressed in pancreatic δ cells and is important for δ cell differentiation (11). In TGP52 cells, HHEX associates with the CRL4B-PRC2 complex Figure 9.…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of this fine-tuned islet circuit by the aberrant regulation of paracrine islet interactions plays an important role in the development of diabetes (1)(2)(3)(4)(5)(6)(7)(8)(9). For example, the loss of the important paracrine factor urocortin 3 (UCN3) in pancreatic β cells caused dysregulation of a somatostatin-mediated negative feedback loop between islet δ and β cells, resulting in aberrant glucoseinduced insulin secretion and contributing to the pathophysiology of diabetes (5,10,11). Recently, the functional importance of pancreatic δ cells in maintaining glucose homeostasis is increasingly being appreciated.…”
Section: Introductionmentioning
confidence: 99%
“…There are limited mature δ-cell markers, and the β-cell-derived δ-like cells all expressed Hhex (Zhang et al, 2014) and somatostatin (Fig. S5F).…”
Section: The Massively Increased δ/δ-Like Cell Number In Mnx1mentioning
confidence: 99%
“…7I). Recent studies from Zhang et al (2014) demonstrated that loss of Hhex in endocrine progenitors and adult δ-cells led to a complete loss of δ-cells, indicating that Hhex is a principal determinant of δ-cell fate during endocrine lineage allocation and postnatal δ-cell fate maintenance. Prior studies in Drosophila and mouse reported that Mnx1, via its tinman repressor domain, acts predominantly as a repressor in neuron subtype determination (Broihier and Skeath, 2002;William et al, 2003;Lacin et al, 2014).…”
Section: Mnx1 As a β-Cell Lineage-allocation Factormentioning
confidence: 99%